Functional Status and Quality of Life Determinants of a Group of Elderly People With Food Insecurity - Baptista, FM (2018)
Background: A good functionality is appointed by the elderly as one of the most important factors for a good quality of life, since it is associated with independency and autonomy. Studies show that elderly with food insecurity have greater limitations in daily living activities (DLA) when compared to food security elderly. Moreover, food insecure elderly are 60% more likely to be diagnosed with depression. We aimed to investigate the potential determinants of functional status (HAQ) and quality of life (EQ-5D-3L) in a sample of elderly with food insecurity. Methods: Forty-one participants with food insecurity were evaluated by a multidisciplinary team, in April and May of 2016 (a baseline cross-sectional study prior to the intervention program). Results: This study demonstrates correlations of functional status and quality of life to such aspects of elderly assessment as age, BMI, manual strength, among others. It was found that manual strength, gender, family income, anxiety, and depression were correlated to quality of life; and that mobility, manual strength, anxiety and gender were correlated to the functional status. After multivariable adjustment, only mobility (beta = -0.220; p <= 0.01) and quality of life (beta = -1.457; p <= 0.01) remained significantly associated with higher levels of functional disability. With regard to quality of life, only the functional status (beta = -0.242; p <= 0.01), the presence of depression (beta = -0.169; p <= 0.05), and family income (beta = 0.185; p <= 0.05) remained significantly associated with health-related quality of life. Conclusions: The study aims to verify the potential determinants of functional status (HAQ) and quality of life (EQ-5D-3L) in a sample of elderly with food insecurity. Even in a small cohort, the study demonstrated that in an elderly population with food insecurity, functional status is associated with mobility and quality of life, and that health-related quality of life is also associated with symptoms of depression and family income. Larger studies in other populations may be useful to confirm these observations.